Aging aggravates cachexia in tumor-bearing mice - Geppert, Julia; Walth, Alina A.; Terrón Expósito, Raúl; Kaltenecker, Doris; Morigny, Pauline; Machado, Juliano; Becker, Maike; Simoes, Estefania; Lima, Joanna D. C. C.; Daniel, Carolin; Berriel Diaz, Mauricio; Herzig, Stephan; et al. (Cancers, 2022)
Background: Cancer is primarily a disease of high age in humans, yet most mouse studies on cancer cachexia are conducted using young adolescent mice. Given that metabolism and muscle function change with age, we hypothesized that aging may affect cachexia progression in mouse models. Methods: We compare tumor and cachexia development in young and old mice of three different strains (C57BL/6J, C57BL/6N, BALB/c) and with two different tumor cell lines (Lewis Lung Cancer, Colon26). Tumor size, body and organ weights, fiber cross-sectional area, circulating cachexia biomarkers, and molecular markers of muscle atrophy and adipose tissue wasting are shown. We correlate inflammatory markers and body weight dependent on age in patients with cancer. Results: We note fundamental differences between mouse strains. Aging aggravates weight loss in LLC-injected C57BL/6J mice, drives it in C57BL/6N mice, and does not influence weight loss in C26-injected BALB/c mice. Glucose tolerance is unchanged in cachectic young and old mice. The stress marker GDF15 is elevated in cachectic BALB/c mice independent of age and increased in old C57BL/6N and J mice. Inflammatory markers correlate significantly with weight loss only in young mice and patients. Conclusions: Aging affects cachexia development and progression in mice in a strain-dependent manner and influences the inflammatory profile in both mice and patients. Age is an important factor to consider for future cachexia studies.
Published: 24 December 2021
Gesehen am 29.04.2022